Morocco : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (International Monetary Fund, 2021)
As in many other countries in the world, the pandemic has exerted a heavy toll on Morocco's population. Its economy has also been hit by a severe drought that affected agriculture output. The authorities' prompt response has helped contain the social and economic damage from the shocks but could not avoid a severe contraction of GDP. The loss of tax revenues deteriorated the fiscal position, while the fall in tourism receipts widened the current account deficit. However, greater access to external borrowing, including the full drawing of the IMF Precautionary and Liquidity Line (PLL) arrangement, has helped maintain international reserves at adequate levels so far in 2020. A gradual economic recovery is expected to begin in 2021, assuming the impact of the drought and the health crisis wane next year. The recent rise in COVID-19 cases, both in Morocco and its main trading partners, suggests that this outlook remains subject to significant downside risks.